Managerial Performance Evaluation and Real Options - Baldenius, Tim; Nezlobin, Alexander A.; Vaysman, Igor (The Accounting Review, 2016)
ABSTRACT In a dynamic setting with demand following a random process, we ask how investment and operating decisions can be delegated to a manager with unknown time preferences. Only the manager observes the demand realization in each period and, therefore, has private information when choosing whether to acquire the productive asset and, subsequently, how to utilize it. We derive accrual accounting-based performance measures under which the manager will make the efficient decisions provided the investment date is exogenously given. We show that in an environment where demand follows a martingale process, the corresponding accounting rules are more decelerated if the firm has the option to idle capacity in case of negative demand shocks. We then describe the limitations of accounting-based performance measures in a scenario where the investment date is endogenously determined, i.e., the firm has an option to wait.